2022
DOI: 10.1002/hbm.26060
|View full text |Cite
|
Sign up to set email alerts
|

The early adolescent brain on music: Analysis of functional dynamics reveals engagement of orbitofrontal cortex reward system

Abstract: Music listening plays a pivotal role for children and adolescents, yet surprisingly few neuroimaging studies have studied the underlying functional dynamics. We used functional magnetic resonance imaging to scan 17 preadolescents aged 10-11 years old while listening to music. We subsequently tracked the occurrence of functional brain networks over time by using a recent method that detects recurrent BOLD phase-locking states: the Leading Eigenvector Dynamics Analysis (LEiDA). In particular, we compared the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 127 publications
(270 reference statements)
0
12
0
Order By: Relevance
“…Music training is a rich and highly engaging experience for children and has the potential to strengthen cognitive skills that are essential for healthy child development. Merely listening to music in a brain imaging scanner elicits activation in the brain's reward circuits in both children (Fasano et al, 2022) and adults (Mas-Herrero et al, 2021;Vuust et al, 2022;Zatorre, 2015). Being internally motivated during learning experiences increases learning capacity and efficiency (Ryan & Deci, 2017), and this greater engagement is reflected in electrical brain activity following musical training (Kraus et al, 2014).…”
Section: Does Music Training Improve Inhibition Control In Children? ...mentioning
confidence: 99%
“…Music training is a rich and highly engaging experience for children and has the potential to strengthen cognitive skills that are essential for healthy child development. Merely listening to music in a brain imaging scanner elicits activation in the brain's reward circuits in both children (Fasano et al, 2022) and adults (Mas-Herrero et al, 2021;Vuust et al, 2022;Zatorre, 2015). Being internally motivated during learning experiences increases learning capacity and efficiency (Ryan & Deci, 2017), and this greater engagement is reflected in electrical brain activity following musical training (Kraus et al, 2014).…”
Section: Does Music Training Improve Inhibition Control In Children? ...mentioning
confidence: 99%
“…We ultimately chose the 4 state estimation as it provided a single state with activity in temporal and mesolimbic regions together. Temporal and mesolimbic region activity has been previously related to auditory reward (Salimpoor et al, 2011, Fasano et al, 2020), including prior analyses of subsets of the present data (Belden et al, 2023, Quinci et al, 2022).…”
Section: Methodsmentioning
confidence: 84%
“…Both younger and older adults showed the highest fractional occupancy in the temporal-mesolimbic network while listening to self-selected music compared to experimenter-selected music. These stimuli were selected by participants to be familiar and well-liked, and auditory-reward network activation for preferred music has been well-documented in prior studies (Salimpoor et al, 2011, Fasano et al, 2020), including on a subset of these data (Quinci et al, 2022). This network was active for experimenter-selected music as well, though to a lesser extent than self-selected music, particularly in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of the method is that it allows calculation of the proportion of time points during an fMRI session assigned to a given RSN, providing a quantitative measure that can be statistically compared between conditions (Alonso Martínez et al, 2020;Cabral, Vidaurre, et al, 2017;Figueroa et al, 2019;Larabi et al, 2020;Magalhães et al, 2021;Wong et al, 2021). This approach allows detection of network-specific modulations; for example, a previous study using LEiDA revealed that psilocybin, a psychoactive molecule, selectively decreases the occupancy of the frontoparietal RSN (associated with executive control), leaving the occupancy of the other RSNs unchanged (Lord et al, 2019), while another study revealed the specific engagement of the orbitofrontal cortex reward system during music listening (Fasano et al, 2022).…”
Section: Dynamic Resting-state Network Analysismentioning
confidence: 99%